Scrum : the art of doing twice the work in half the time - Sutherland, Jeff, 1941- (Penguin Books, 2024)
Scrum is the reason that Amazon can launch a new feature on its website every day. It''s how the FBI finally created a massive terrorist-tracking database. It has revolutionised productivity and team-building in industries as varied as the military and healthcare in major hospitals. The reason for the rapid embrace of Scrum across so many disciplines is simple: organisations that implement the Scrum method typically double productivity and quality - and sometimes the increase can be as much as twelve-fold. Now, in this new 10th Anniversary edition, JJ and Jeff Sutherland take the project management system that everyone continues to talk about even further, sharing brand new case studies and anecdotes, from how John Deere used Scrum to increase their supply chain during the pandemic despite nationwide shutdowns, to how the UK ministry of defence is using Scrum across their entire military in response to emerging threats like Russia and China, and how agile and scrum teams are collaborating with AI to be more effective than both humans or robots alone. A lot has changed in the last ten years, but the good news is that the Scrum framework is as adaptable as it is effective. Filled with actionable tips on how to build teams, set goals and monitor progress, it also includes brand-new research on the psychology of how we work and stay motivated.